Phase II Trial of Neoadjuvant Carboplatin and Nab‐Paclitaxel in Patients with Triple‐Negative Breast Cancer. (8th November 2020) - Yuan, Yuan; Lee, Jin Sun; Yost, Susan E.; Li, Sierra Min; Frankel, Paul H.; Ruel, Christopher; Schmolze, Daniel; Robinson, Kim; Tang, Aileen; Martinez, Norma; Stewart, Daphne; Waisman, James; et al.
Abstract: Background: In this phase II clinical trial, we evaluated the efficacy of the nonanthracycline combination of carboplatin and nab‐paclitaxel in early stage triple‐negative breast cancer (TNBC). Patients and Methods: Patients with newly diagnosed stage II–III TNBC ( n = 69) were treated with neoadjuvant carboplatin (area under the curve 6) every 28 days for four cycles plus nab‐paclitaxel (100 mg/m 2 ) weekly for 16 weeks. Pathological complete response (pCR) and residual cancer burden (RCB) were analyzed with germline mutation status, tumor‐infiltrating lymphocytes (TILs), TNBC molecular subtype, and GeparSixto immune signature (GSIS). Results: Sixty‐seven patients were evaluable for safety and response. Fifty‐three (79%) patients experienced grade 3/4 adverse events, including grade 3 anemia (43%), neutropenia (39%), leukopenia (15%), thrombocytopenia (12%), fatigue (7%), peripheral neuropathy (7%), neutropenia (16%), and leukopenia (1%). Twenty‐four patients (35%) had at least one dose delay, and 50 patients (72%) required dose reduction. Sixty‐three (94%) patients completed scheduled treatment. The responses were as follows: 32 of 67 patients (48%) had pCR (RCB 0), 10 of 67 (15%) had RCB I, 19 of 67 (28%) had RCB II, 5 of 67 (7%) had RCB III, and 1 of 67 (2%) progressed and had no surgery. Univariate analysis showed that immune‐hot GSIS and DNA repair defect (DRD) were associated with higher pCR with odds ratios of 4.62 ( p = .005) and 4.76 ( p = .03), respectively, and with RCB 0/I versus RCB II/III with odds ratio 4.80 ( p = .01). Immune‐hot GSIS was highly correlated with DRD status ( p = .03), TIL level ( p < .001), and TNBC molecular subtype ( p < .001). After adjusting for age, race, stage, and grade, GSIS remained associated with higher pCR and RCB class 0/I versus II/III with odds ratios 7.19 (95% confidence interval [CI], 2.01–25.68; p = .002) and 8.95 (95% CI, 2.09–38.23; p = .003), respectively. Conclusion: The combination of carboplatin and nab‐paclitaxel for early stage high‐risk TNBC showed manageable toxicity and encouraging antitumor activity. Immune‐hot GSIS is associated with higher pCR rate and RCB class 0/1. This study provides an additional rationale for using nonanthracycline platinum‐based therapy for future neoadjuvant trials in early stage TNBCs. Clinical trial identification number : NCT01525966 Implications for Practice: Platinum is an important neoadjuvant chemotherapy agent for treatment of early stage triple‐negative breast cancer (TNBC). In this study, carboplatin and nab‐paclitaxel were well tolerated and highly effective in TNBC, resulting in pathological complete response of 48%. In univariate and multivariate analyses adjusting for age, race, tumor stage and grade, "immune‐hot" GeparSixto immune signature (GSIS) and DNA repair defect (DRD) were associated with higher pathological complete response (pCR) and residual cancer burden class 0/1. The association of immune‐hot GSIS with higher pCR holds promise for de‐escalating neoadjuvant chemotherapy for patients with early stage TNBC. Although GSIS is not routinely used in clinic, further development of this immune signature into a clinically applicable assay is indicated. Abstract : Metastatic triple‐negative breast cancer is associated with poor clinical outcomes, largely due to a lack of effective targeted therapy. This article reports the results of a phase II trial evaluating the efficacy of neoadjuvant carboplatin plus nab‐paclitaxel in patients with stage II–III triple‐negative breast cancer.